Antibacterial Activity of Chitosan Against the Asian Pear Pathogenic Bacterium Bacillus pumilus - Zhou, Q.; Qiu, H.; Shan, C.L.; Li, B.; Ibrahim, M.; Xie, G.L.; Wang, Y.L.; Sun, G.C. (Asian Journal of Chemistry, 2013)
In this study, the antibacterial activity of chitosan against the Asian pear pathogenic bacterium Bacillus pumilus was investigated. Results showed that the bacterial cell numbers increased with the increase of incubation time and the strength of Luria-Bertani broth in the absence of chitosan. However, chitosan solution at 0.01, 0.05 and 0.10 mg/mL markedly inhibited the growth of B. pumilus strains B0703 and B0706, while the antibacterial activity of chitosan solution increased with the increase of chitosan concentration, incubation time and the strength of Luria-Bertani broth regardless of the tested bacterial strains. Overall, the results indicated that chitosan may be a promising bactericide in fruit production.